Scripture, Church, and Authority: Harmonization of the Doctrine of the Sufficiency of the Bible with Church History - Reynaldi, Christian (Veritas: Jurnal Teologi dan Pelayanan, 2019)
Scripture as the Word of God is an undeniable creed in Christianity. One of many implications from this belief is the doctrine of the sufficiency of scripture. Scripture is deemed sufficient enough to teach man toward salvation and full obedience unto God. Nevertheless how sufficiency of scripture is defined and confined, because it seems impossible to theologize without any supplements. One of those supplements that interest me is church tradition because people tend to contrast church tradition and doctrine of the sufficiency of scripture. However, shall two of them be contrasted? This writings will answer harmonization between doctrine of sufficiency of scripture and church tradition. I argue that doctrine of sufficiency of scripture never nulify church tradition. The absolute church tradition that use in theologizing as a christian is Rule of Faith, as a summary of christian faith since early church. Another church traditions need to be evaluated whenever they are used in theologizing.